Google cloud platform professional cloud architect. - Dantas, Victor (Complete video course (Pearson IT Certification)., 2023)
10+ Hours of Video Instruction 10+ hours of deep-dive video training designed to get you fully prepared to pass the Google Cloud Platform Professional Cloud Architect exam Get the knowledge you need to pass the Google Cloud Platform Professional Cloud Architect exam in this all-new video course. This course is a complete study resource to help you build the skills you need as you work your way through the course. Explore every exam objective on the Professional Cloud Architect exam and learn how to design a robust cloud solution architecture on the Google Cloud Platform. Trainer, author, and cloud expert Victor Dantas uses targeted demos, sample exam question breakdowns, and sample case study reviews to ensure you are fully prepared for the exam. The Google Cloud Platform Professional Cloud Architect Complete Video Course does a deep dive into ensuring solution and operations reliability, designing for security and compliance, managing and provisioning the cloud solution infrastructure, and analyzing and optimizing technical and business processes with Google Cloud. You will also learn best practices for successful deployments and how to design network, storage, and compute resources. Topics include Module 1: Professional Cloud Architect Certification overview Module 2: Designing and planning a cloud solution architecture Module 3: Managing and provisioning a solution infrastructure Module 4: Designing for security and compliance Module 5: Analyzing and optimizing technical and business processes Module 6: Managing implementation Module 7: Ensuring solution and operations reliability About the Instructor Victor Dantas has a PhD in Software-Defined Networking (SDN) and cloud systems, and is currently a Sr. Cloud Solutions Architect. He has professional cloud certifications from Google Cloud, Azure, and AWS. With a background ranging from software development and systems engineering to technology consulting, he has accumulated experience in software engineering, cloud migrations, hybrid cloud infrastructure, cloud solutions architecture, and Agile/DevOps practices working with organizations of all sizes. Victor also writes practical guides and labs on cloud computing and is the author of Architecting Google Cloud Solutions (Packt, 2021). Beyond cloud, his interests include Big Data, AI/Machine Learning and Internet-of-Things (IoT). Skill Level Intermediate Advanced Learn How To Design and plan a cloud solution architecture Manage and provision a solution infrastructure Design for security and compliance Analyze and optimize technical and business processes Manage implementation Ensure solution and operations reliability Who Should Take This Course IT professionals with 3+ years of experience in the industry including 1+ years designing and managing solutions using Google Cloud. Cloud or Solutions Architects without experience with Google Cloud but experienced in other cloud platforms may also take this course. Cloud engineers looking to deepen their skills in architecting google cloud solutions will also benefit from this course. Course Requirements Knowledge of cloud infrastructure foundations: storage, compute, databases, networking, and security. Basic familiarity with the Google Cloud Platform. Foundational system design knowledge. Basic proficiency in one programming language, although not required, is recommended. About Pearson Video Training Pearson publishes expert-led video tutorials covering a wide selection of technology topics designed to teach you the skills you need to succeed. These professional and personal technology videos feature world-leading author instructors published by your trusted technology brands: Addison-Wesley, Cisco Press, Pearson IT Certification, Sams, and Que. Topics include: IT Certification, Network Security, Cisco Technology, Programming, Web Development, Mobile Development, and more. Learn more about Pearson Video training at http://www.informit.com/video.